Two new species of Caulleriella (Polychaeta, Cirratulidae) from Argentina - Elías,Rodolfo (2008)
Caulleriella bremecae and C. galeanoi (Polychaeta: Cirratulidae) are newly described from Mar del Plata, Argentina (38ºS, 57ºW). Both species have small, red-pigmented nuchal organs (lateral "eyes") on the prostomium. Caulleriella bremecae sp. nov. is further characterized by a peristomium without annulations except for a narrow anterior dorsal fold, posterior part of peristomium extending posterodorsally over chaetiger 1, latter extending posterodorsally over chaetiger 2 and with slightly separated grooved palps arising middorsally; notochaetae of chaetigers 1-23 all smooth capillaries, thereafter with six bidentate sigmoid hooks and 3-4 capillaries, both types fewer on last 4-5 chaetigers; neurochaetae of chaetigers 1-2 comprised of 8 bidentate hooks and 1-2 capillaries, thereafter only bidentate hooks, decreasing in number posteriorly. The species is frequent and abundant throughout the year in the intertidal mussel beds situated 200-700m from the sewage outfall of Mar del Plata city. Caulleriella galeanoi sp. nov. is characterized by a peristomium with three annulations dorsally, with grooved palps arising from annulus 3, and by smooth capillary chaetae in noto- and neuropodia of chaetigers 1-2. Bidentate hooks are present in neuropodia from chaetiger 3, numbering 5-6 in anterior and middle chaetigers, 1-3 in posterior ones. Notopodia have 3-6 pairs of smooth capillary chaetae, decreasing in number posteriorly. From chaetiger 13-20, notopodia with 1-2 capillary chaetae and 1-2 bidentate hooks. Specimens held in aquaria supplied with water and the green alga Vaucheria sp. (Vaucheriaceae) from the intertidal zone reproduced asexually by fission. Gametes were not observed in any specimens.